BANK PERSONNEL MANAGEMENT AS A MEANS OF PREVENTING INTERNAL THREATS - Ковальчук, Вероніка; Дейно, Євгенія (Socio-economic relations in the digital society, 2020)
The article explores the peculiarities of personnel management in the context of preventing internal bank threats. For greater understanding, key concepts related to this topic have been considered, namely concepts such as «personnel risks» and «personnel security». The practice of the domestic banking system suggests that most banking problems are concentrated in the field of HR. This situation today deepen such factors as lack of philosophy and the development missions of most banks; incomprehension features and specifics of the bank’s staff; heterogeneity of bank staff as a term work in financial and banking structures, and for received basic education; strengthening interbank competition, including in the plane labor relations; lack of existing technologies of selection and hiring of personnel bank; weakening of control functions over actions staff in banks and middle managers; underestimation of motivational aspects in management-labor resources, growing demands on a high level of professionalism and communication abilities of bank employees. The article on the example of JSC «Ukreksimbank» proves that the development of recommendations for improving the personnel management system of any enterprise should rely on the analysis of its external and internal environment, analysis of the current state of the human resources management system. Despite the high level of thoughtfulness of the Bank’s existing personnel management system, it has been identified that it still contains problematic aspects that need further elaboration. The key ones are staff turnover and a mediocre level of employee loyalty to the enterprise, which in turn pose a threat to the banking institution. It is concluded that personnel safety should be directed on the one hand to reduce threats from personnel and on the other — to stimulate his effective work.
Keywords: bank personnel management; banking security; internal bank threats; economic security; personnel security; personnel risks